Case Report: Coronaro-bronchial fistula vascularizing a squamous cell lung cancer - Ntshaykolo, Chloe; Fave, Thomas; Benic, Clement; Boizet, Antoine; Geier, Margaux; Nicol, Pierre-Philippe; Descourt, Renaud (Frontiers in Cardiovascular Medicine, 2023)
Coronary fistulas are rare, having been described for the first time by Krauss in 1865 in postmortem. They are commonly asymptomatic and can be caused by congenital or acquired malformations. We present the case of a 65-year-old patient who was treated for squamous cell lung cancer with chemoimmunotherapy and presented with angina. The coronary angiography showed a coronaro-bronchial fistula that arises from a branch of the right coronary artery and is associated with lung cancer.